A validation model for non-lexical routing protocols - Sarakbi, Bakr; Khayou, Hussein (ACADEMIC PRESS LTD- ELSEVIER SCIENCE LTD, 2017)
Routing protocols properties form an essential topic of research. Ensuring that a routing protocol is stable, loop free and reaches the global optimal topology solution is needed for both evaluating it and doing the required enhancements for it. There exist several trials in previous researches to enhance routing protocols. Those works depend on either theoretical models or simulation to validate their results. Existing validation models target lexical based routing metrics only. In this work, we propose a validation model for non-lexical routing metrics (such as Enhanced Interior Gateway Routing Protocol - EIGRP). Our validation model is based on abstract algebra. It helps in validating necessary routing properties and enhancing existing routing protocols in such a way that makes them meet those properties.
Keywords: Routing protocols; Algebra; Routing algorithms; Networks; Semirings; Convergence; Routing stability; Loop free routing